A toolkit to aid in the education and training of supply chain members for the efficient distribution of the COVID-19 vaccine : a South African case - Stofberg, Suzanne (Stellenbosch : Stellenbosch University, 2022)
Thesis (MCom)--Stellenbosch University, 2022.